APPROACHING THE HARD TO REACH POPULATION: THE EXPERIENCE OF DATA COLLECTION AMONG UNWED MOTHERS IN MALAYSIA - Saim, Nor Jana (International Journal of Psychosocial Rehabilitation, 2020)
The article focuses on the challenges of data collection among hard to reach population in Malaysia; unwed mother. The data was gathered during the narrative interviews of 17 unwed teenage mothers, aged between 12 to 18 years during their placement in shelter homes. The results showed that the researchers were having difficulties to build up rapport with the research participants especially at the initial stage of data collection. Participation of the researchers in the participants’ activities was considered crucial in making the researchers as an ‘insider’ to the research participants. Creating initial rapport, restriction to choose participants, multiple sessions of interviews, low education level, talkative participants and attention seeking participants are among the challenges during the data collection. In addition, supportive and conducive environment for conducting the interview also important to make the data collection successful. In Malaysia the presence of marginalized groups is often neglected and therefore it is important to build a trustworthy relationship between the researchers and participants. Considering that, it enables the researchers to depicting the issues of marginalized groups and represent their voices in the studies.